(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Herpes virus infection is a cause of inflammatory corneal diseases in 20-57 % of cases. To date, due to the lack and high cost of donor material in Ukraine, approbation of new material for keratoplasty is of great relevance. Purpose. To report a case of successful using a stromal corneal transplant for therapeytic keratoplasty in a patient with herpitic keratitis. Material and Methods. Visual acuity testing, standard ophthalmic examination, microbiology study. Results. Using lyophilized stromal layers made it possible to prevent corneal perforation in a patient with herpetic keratitis. Early operative intervention made it possible to preserve visual function and to avoid severe complications. Conclusions. If urgent keratoplasty is required and keratobioimplant is not available/affordable, lyophilized stromal layers of the cornea with the Descemet’s membrane can serve as an alternative material for therapeutic tectonic keratoplasty and can prevent development of severe keratitis complications including descemetocele, corneal perforation etc.